2009
DOI: 10.1074/jbc.c109.009522
|View full text |Cite
|
Sign up to set email alerts
|

X-linked Inhibitor of Apoptosis Protein (XIAP) Regulates PTEN Ubiquitination, Content, and Compartmentalization

Abstract: Apoptotic cell death plays a normal role in various physiological processes, and deregulated apoptosis is a hallmark of several diseases, including cancer. Cell fate is dictated by the balance between pro-and antiapoptotic factors. Akt is one of these antiapoptotic factors, which must be activated through phosphorylation. The phosphorylation of Akt has previously been shown to be promoted by X-linked inhibitor of apoptosis protein (XIAP), another antiapoptotic protein dictating the fate of normal and cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 25 publications
(26 reference statements)
2
111
2
1
Order By: Relevance
“…Previous studies have shown the regulatory mechanism for PTEN stability. PTEN can be ubiquitinated and degradaded by several ubiquitin E3 ligases, such as NEDD4 and the X-linked inhibitor of apoptosis protein Wang et al, 2007;Van Themsche et al, 2009). Phosphorylation of PTEN by casein kinase 2 or GSK3b also controls PTEN stability by promoting ubiquitination (Torres and Pulido, 2001;Al-Khouri et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the regulatory mechanism for PTEN stability. PTEN can be ubiquitinated and degradaded by several ubiquitin E3 ligases, such as NEDD4 and the X-linked inhibitor of apoptosis protein Wang et al, 2007;Van Themsche et al, 2009). Phosphorylation of PTEN by casein kinase 2 or GSK3b also controls PTEN stability by promoting ubiquitination (Torres and Pulido, 2001;Al-Khouri et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct inhibition of caspase activation in vivo, XIAP can modulate apoptosis through alternative mechanisms associated with its function as an E3 ubiquitin ligase (21,52). Further studies to delineate these mechanisms could provide additional insight into the pathobiology of fibrotic wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…The NEDD4-1 and XIAP ubiquitin E3 ligases ubiquitinate PTEN. [50][51][52] PTEN phosphatase activity is also regulated by oxidization. At the center of PTEN's phosphatase catalytic site is a cysteine nucleophile, which is subject to oxidization.…”
Section: Pseudo-pten and Other Oncogenes Decoys For Mirnasmentioning
confidence: 99%